Resting functional connectivity reveals residual functional activity in Alzheimer's disease. - Zamboni, G; Wilcock, G; Douaud, G; Drazich, E; McCulloch, E; Filippini, N; Tracey, I; Brooks, J; Smith, S; Jenkinson, M; Mackay, C (2013)
BACKGROUND: Functional magnetic resonance imaging (fMRI) has great potential for measuring mechanisms of functional changes in Alzheimer's disease (AD) and mild cognitive impairment, but task fMRI studies have produced conflicting results, partly due to failure to account for underlying morphological changes and to variations in patients' ability to perform the tasks. Resting fMRI has potential for assessing brain function independently from a task, but greater understanding of how networks of resting functional connectivity relate to the functioning of the brain is needed. We combined resting fMRI and task fMRI to examine the correspondence between these methods in individuals with cognitive impairment. METHODS: Eighty elderly (25 control subjects, 25 mild cognitive impairment, 30 AD) underwent a combined multimodal magnetic resonance imaging protocol including task fMRI and resting fMRI. Task fMRI data were acquired during the execution of a memory paradigm designed to account for differences in task performance. Structural and physiological confounds were modeled for both fMRI modalities. RESULTS: Successful recognition was associated with increased task fMRI activation in lateral prefrontal regions in AD relative to control subjects; this overlapped with increased resting fMRI functional connectivity in the same regions. CONCLUSIONS: Our results show that task fMRI and resting fMRI are sensitive markers of residual ability over the known changes in brain morphology and cognition occurring in AD and suggest that resting fMRI has a potential to measure the effect of new treatments.